Tengku Muhammad Saleh: Ulama Generasi Terakhir Kerajaan Riau Lingga, 1901-1966 - Arman, Dedi; Swastiwi, Anastasia Wiwik (Jurnal Sejarah Indonesia, 2024)
At the end of the 19th century from the Riau Lingga Kingdom appeared a number of scholars, such as King Ali Haji, Raja Ali Kelana, King Khalid Hitam, and a number of other names who settled on Penyengat Island. The majority of these scholars are from the nobility of Riau Lingga Kingdom and are of Bugis blood. At the beginning of the 20th century, there appeared a Malay cleric of noble Riau Lingga Kingdom named Tengku Muhammad Saleh (TMS) who settled on Lingga Island, the area that became the center of Riau Lingga Kingdom in 1787-1900. This paper examines the biography of Tengku Muhammad Saleh (TMS): The Last Generation Ulama of Riau Lingga Kingdom 1901-1966. From the research, it was concluded that TMS was a nobleman and cleric of the Riau Lingga Kingdom who was anti- the Dutch government. Resistance against the Dutch was carried out through criticism through writing and also rejected positions in the government of the Riau Lingga Kingdom. He was arrested by the Dutch because he was considered a Japanese spy and taken to Batavia but was able to escape. During the Japanese occupation, TMS was appointed as a judge of the Sharia Court in Lingga. TMS's formal education is not high, but his figure is highly respected because he gave birth to a number of works, including the book Nur al Salah which is currently taught in mosques in Lingga. A figure of Hamka's caliber had come to Lingga to meet TMS in 1957. He actively preached from the islands and settled in his hometown.